PERCEPCIÓN DE LAS PERSONAS SORDAS FRENTE A SU NO INCLUSIÓN LABORAL EN LAS ORGANIZACIONES DE VILLAVICENCIO (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
In Villavicencio there is a high percentage of deaf people who are of working age, but according to the latest projection of the National Institute for the Deaf (INSOR) on the Census (DANE, 2021), only 6% are in a state of activity, where 0.1% work in the livestock sector, 2% work in the agricultural sector, 1.9% work in the service sector, 1.5% work in the commercial sector, and 0.5% work in the industrial sector. While the remaining 94% are in a situation of labor inactivity, this is due to various factors that are expected to be found in the result of this investigation.             The research project focused on a field study, through a type of descriptive research, which seeks to publicize the problems faced in the workplace by people who belong to the deaf community, in which the different reasons will be analyzed for which they have the perception of being discriminated against and excluded from companies; which will seek to mitigate with various strategies, which go hand in hand with the improvement of their learning, professional training and handling of Spanish in written form as a second language.
Keywords: Deaf, INSOR, professional training, organization, quality of life.